2012
DOI: 10.1038/modpathol.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic complexity of T regulatory subsets in patients with B-chronic lymphocytic leukemia

Abstract: Increased numbers of T regulatory (Treg) cells are found in B-chronic lymphocytic leukemia, but the nature and function of these Tregs remains unclear. Detailed characterization of the Tregs in chronic lymphocytic leukemia has not been performed and the degree of heterogeneity of among these cells has not been studied to date. Using 15-color flow cytometry we show that Treg cells, defined using CD4, CD25, and forkhead box P3 (FOXP3), can be divided into multiple complex subsets based on markers used for naïve,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 46 publications
2
35
0
1
Order By: Relevance
“…We have recently been shown that the frequencies of both CD8 + FoxP3 + and future science group www.futuremedicine.com CD8 + CD25 + FoxP3 + Tregs were increased in CLL patients and correlated with disease progression [4]. Other study has also been confirmed our experience [77]. Nunes et al have also shown emergence of CD8 + PD-1 + replicative senescent phenotype in early stage CLL and its correlation with disease progression [78].…”
Section: Tregs In Cllsupporting
confidence: 85%
See 3 more Smart Citations
“…We have recently been shown that the frequencies of both CD8 + FoxP3 + and future science group www.futuremedicine.com CD8 + CD25 + FoxP3 + Tregs were increased in CLL patients and correlated with disease progression [4]. Other study has also been confirmed our experience [77]. Nunes et al have also shown emergence of CD8 + PD-1 + replicative senescent phenotype in early stage CLL and its correlation with disease progression [78].…”
Section: Tregs In Cllsupporting
confidence: 85%
“…The functional capacity of Tregs is another important issue in the immunobiology of Tregs in CLL patients which is investigated in our [4] and some other studies [23,77]. The first report regarding the Tregs function in CLL was reported by Giannopoulos et al which showed that the higher frequencies of Tregs were correlated with decreased T-cell responses against viral and tumor antigens [24].…”
Section: Tregs In Cllmentioning
confidence: 94%
See 2 more Smart Citations
“…Before the final panel was assembled, numerous clones of antibodies and fluorochrome combinations of antibodies were tested in order to optimize the identification of cell populations and to prevent unnecessarily high amounts of spectral compensation. The feasibility of developing a panel of multiple 15-color tubes has been demonstrated in our laboratory, and the panel’s utility in describing complex alterations of the immune system in the context of disease and vaccination has been demonstrated (Biancotto et al 2012a, b). …”
Section: Technical Issues In Polychromatic Immunophenotypingmentioning
confidence: 99%